Karakteristik dan Uji Aktivitas Antiosidan Ekstrak Kolagen Sisik Ikan Gabus (Channa sp.) - Su'aida, Nily; Ridha, ainur; Soemarie, Yulistia Budianti (BORNEO JOURNAL OF PHARMASCIENTECH, 2025)
This study aims to isolate collagen from the scales of snakehead fish (Channa sp.) and evaluate the antioxidant activity of the extracted collagen. Collagen was isolated using a 0.5 M acetic acid method, involving dissolution and purification procedures. The collagen extract was characterized using FTIR analysis to detect functional groups and phytochemical tests to identify active compounds. Antioxidant activity was assessed using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method to measure free radical scavenging potential. The results indicated that the collagen extract from snakehead fish scales contains bioactive compounds with significant antioxidant activity. The IC₅₀ values demonstrated a strong ability to neutralize free radicals, showing higher potency than the control. FTIR analysis detected hydroxyl (3330.21 cm⁻¹), methyl (2111.83 cm⁻¹), and carbonyl (1635.85 cm⁻¹) groups as characteristic phytochemical components of Channa sp. collagen extract. The IC₅₀ values at different concentrations were classified as very strong at low concentrations (25%), strong at moderate concentrations (50%), and moderate at higher concentrations (75%). The antioxidant activity of snakehead fish scale extract was very strong at lower concentrations but decreased as the concentration increased